The Psychological Impact of Parental Divorce on Adolescents: A Comprehensive Analysis of Coping Mechanisms and Support Networks - VB, Devapramod (Sinergi International Journal of Psychology, 2024)
Parental divorce is a significant life event that affects the emotional well-being of adolescents, often leading to psychological distress, social difficulties, and long-term identity development challenges. This study explores the emotional dynamics of adolescents following parental divorce using a qualitative case study approach. Data were collected through in-depth interviews with 12 participants, including adolescents, divorced parents, and counselors. Thematic analysis was employed to identify key patterns in the emotional experiences, coping mechanisms, and support systems of affected adolescents. The results indicate that adolescents exhibit a spectrum of emotional responses, including sadness, frustration, and confusion. While some adolescents utilize adaptive coping strategies such as journaling and peer support, others engage in avoidance behaviors, which may exacerbate their distress. Parental involvement and open communication were found to be pivotal in facilitating better emotional adjustment, whereas the lack of support contributed to prolonged emotional struggles. Furthermore, school-based interventions and professional counseling play crucial roles in mitigating the negative psychological effects of parental divorce. This study contributes to the understanding of adolescent resilience in the face of parental divorce and highlights the need for comprehensive support systems, including parental guidance, peer networks, and institutional interventions. Future research should examine the long-term impact of divorce on adolescent identity and explore culturally sensitive approaches to post-divorce counseling.